Chitosan Nanoparticles Strengthen Vγ9Vδ2 T-Cell Cytotoxicity Through Upregulation Of Killing Molecules And Cytoskeleton Polarization - Lin L (Dove Medical Press, 2019)
Li Lin,1,2,* Junyi He,2,* Jiawei Li,2 Yan Xu,2 Jingxia Li,2 Yangzhe Wu1,2 1Zhuhai Precision Medical Center, Zhuhai People’s Hospital, Zhuhai Hospital Affiliated with Jinan University, Jinan University, Zhuhai, Guangdong 519000, People’s Republic of China; 2The Biomedical Translational Research Institute, Faculty of Medical Science, Jinan University, Guangzhou, Guangdong 510632, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yangzhe WuZhuhai Precision Medical Center, Zhuhai People’s Hospital, Zhuhai Hospital Affiliated with Jinan University, Jinan University, Zhuhai, Guangdong 519000, People’s Republic of ChinaTel +86 020 8522 2787Email tyzwu@jnu.edu.cnBackground: During the past few years, immune cell therapy for malignant cancer has benefited a considerable amount of patients worldwide. As one of several promising candidates for immunotherapy, Vγ9Vδ2 γδ T cells have many unique biological advantages, such as non-MHC restriction and have been noted as the earliest source of IFN-γ. However, potentiating anti-tumor functions of γδ T cells has become of particular interest to researchers studying γδ T cell applications.Purpose: In this study, we proposed a nanotechnology-based methodology for strengthening γδ T cell functions.Methods: As a type of reliable, biocompatible material, chitosan nanoparticles (CSNPs) were used to enhance anti-tumor immunity of γδ T cells.Results: First, we found that the size of prepared CSNPs distributed 50 to 100 nm, and that CSNPs had optimal immunocompatibility. Then, we observed that CSNPs could induce α-tubulin cytoskeleton polarization and rearrangement, correlating with a higher killing ability of γδ T cells. Furthermore, we revealed that CSNPs could enhance Vγ9Vδ2 T cell anti-tumor functions by upregulating killing of related receptors, including NKG2D, CD56, FasL, and perforin secretion.Conclusion: Our work provided evidence of application for CSNPs based bio-carrier in immunotherapy. More importantly, we proposed a new strategy for enhancing γδ T cell anti-tumor activity using nanobiomaterial, which could benefit future clinical applications of γδ T cells.Keywords: chitosan nanoparticles, Vγ9Vδ2 γδ T cell, cytotoxicity, anti-tumor activity